2017
DOI: 10.1080/09546634.2017.1328099
|View full text |Cite
|
Sign up to set email alerts
|

A case series of imatinib-induced generalized hypopigmentation and progression of existing acquired dermal melanocytosis

Abstract: Imatinib mesylate is a tyrosine kinase inhibitor used in the treatment of oncological conditions, including chronic myeloid leukemia and gastrointestinal stromal tumors. The most frequent dermatological side effect reported is pigmentary abnormalities. We report a case series of three Asian Chinese females with preexisting acquired dermal melanocytosis that progressed after initiation of imatinib treatment, and concurrently developed generalized hypopigmentation of the skin. All three patients had similar hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Imatinib mesylate is a tyrosine kinase inhibitor (TKI) used to treat chronic myeloid leukaemia and gastrointestinal stromal tumours among other cancers. Dermatologic skin manifestations of imatinib are commonly reported and include pigmentary abnormalities such as hyper‐ and hypopigmentation 1 . Here, we present the first case of eruptive melanocytic nevi (EMN) induced by imatinib, a phenomenon previously reported with other TKIs.…”
Section: Introductionmentioning
confidence: 79%
“…Imatinib mesylate is a tyrosine kinase inhibitor (TKI) used to treat chronic myeloid leukaemia and gastrointestinal stromal tumours among other cancers. Dermatologic skin manifestations of imatinib are commonly reported and include pigmentary abnormalities such as hyper‐ and hypopigmentation 1 . Here, we present the first case of eruptive melanocytic nevi (EMN) induced by imatinib, a phenomenon previously reported with other TKIs.…”
Section: Introductionmentioning
confidence: 79%
“…However, skin and hair color changes related to imatinib for GIST tumor are relatively rare [8]. On literature review, there were only 3 cases found specifically of hypopigmentation with imatinib used for GIST tumors in patients without germline KIT mutations causing familial GIST [9,10,15]. Results are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Imatinib mesylate, a tyrosine kinase inhibitor, is used for treatment of oncological conditions, such as chronic myeloid leukemia (CML) and gastrointestinal stromal tumor 1 . It inhibits tyrosine kinase encoded by the bcr-abl, c-kit, and platelet-derived growth factor receptor oncogenes 2 3 .…”
mentioning
confidence: 99%
“…ABNOM, a kind of ADM, is characterized by symmetrical blue-brown macules, most frequently involving facial lesions in Asian women with histopathological findings of irregularly-shaped bipolar melanocytes dispersed in the papillary and mid dermis, particularly in the subpapillary dermis. These dormant melanocytes could be later reactivated by various factors like inflammation, local trauma, sunlight, drugs, or hormonal stimulations 1 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation